2016
DOI: 10.22260/isarc2016/0036
|View full text |Cite
|
Sign up to set email alerts
|

A Framework of Lift Virtual Prototyping (LVP) Approach for Crane Safety Planning

Abstract: -Many crane accidents occur due to a lack of understanding of potential constraints present on lift sites, especially the spatial conflicts with inadequate clearance to surrounding obstructions. Even the most thorough lift plans can be compromised by changes in lift sites such as a newly-erected frame in the crane workspace or a sudden presence of another equipment. Therefore, it is critical for the lift crew (i.e., planner, rigger, signalman, operator) to be aware of the condition and potential constraints in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Researchers developed a virtual prototyping platform to improve crane safety. In this platform, a lift crew, consisting of a planner, rigger, signalman, and operators, virtually perform lifting operations [59]. The results indicate that this tool can improve the operator's confidence and safety.…”
Section: Ar/vr In Aecmentioning
confidence: 95%
“…Researchers developed a virtual prototyping platform to improve crane safety. In this platform, a lift crew, consisting of a planner, rigger, signalman, and operators, virtually perform lifting operations [59]. The results indicate that this tool can improve the operator's confidence and safety.…”
Section: Ar/vr In Aecmentioning
confidence: 95%
“…For instance, overhead crane [11] and bridge crane [12] operator training systems based on virtual reality are discussed. Some other efforts are made to evaluate and enhance safety conditions in this regard [13]- [15]. However, authors have not found any specific investigation in the application of VR technology in heavy lift planning process of mobile cranes.…”
Section: Related Workmentioning
confidence: 99%